Follow-up outcomes of hybrid procedures for thoracoabdominal aortic pathologies with special focus on graft patency and late mortality - Bianchini Massoni, Claudio; Geisbüsch, Philipp; Gallitto, Enrico; Hakimi, Maani; Gargiulo, Mauro; Böckler, Dittmar (Journal of vascular surgery, 2014)
Objective - The purpose of this study was to analyze midterm results of bypass patency and overall and aortic-related mortality rates of hybrid aortic procedures for thoracoabdominal aortic pathologies. - Methods - A retrospective study was performed considering prospectively collected data in two centers. From January 2001 to December 2012, 45 patients (33 men; mean age, 67.8 ± 7.6 years) received hybrid aortic procedures for thoracoabdominal aortic diseases (31 atherosclerotic aneurysms, 7 chronic expanding type B aortic dissections, 2 penetrating aortic ulcers, and 5 pseudoaneurysms), corresponding to 155 revascularized visceral abdominal arteries. Elective/emergency and staged/simultaneous approaches were 31 of 14 and 28 of 17, respectively. Patient demographics, clinical risk factors, and aortic morphological and procedural data were collected. End points were technical success, 30-day morbidity, reintervention and mortality, bypass graft patency, freedom from reintervention, and overall and aortic-related mortality during midterm follow-up. Mean follow-up was 2.2 ± 2.4 years. - Results - Technical success was achieved in 86.6% (39/45) of patients. Thirty-day morbidity rate was 60% (paraplegia/paraparesis: 13.3%, stroke: 6.7%, renal failure: 31.3%, permanent dialysis: 4.4%). Thirty-day freedom from reintervention rates were 67.1% and 78.5%, respectively. Thirty-day occlusion of revascularized visceral vessels occurred in 11 (7.1%, 11/155) target arteries. In-hospital mortality rate was 24.4%. Primary graft patency after 1, 2, and 4 years was 89.7%, 85.3%, and 79%, respectively. Bypass thrombosis or stenosis developed in nine (6.8%, 9/132) vessels during follow-up. Of these, three patients required reintervention and one died. Freedom from reintervention rates after 1, 2, and 4 years were 45.6%, 45.6%, and 34.2%, respectively. Overall and aortic-related mortality rates after 1, 2, and 4 years were 32.6%, 41.4%, and 45.3% and 9.1%, 13.9%, and 13.9%, respectively. - Conclusions - A hybrid procedure for thoracoabdominal aortic pathologies in high-risk patient is feasible but carries a significant rate of early and midterm reintervention and death. Long-term surveillance of the visceral bypass is necessary because one-third of the patients will have bypass-related complications.